Engine Performance and Emission of a Twin Cylinder Diesel Engine Fuelled with Biodiesel and Ethanol Blends with the Fraction of Fuel Additives - Verma, Ankit; Thamotharan, C.; Naveenchandran, P.; Raja, E. (International Journal of Psychosocial Rehabilitation, 2018)
A comprehensive study on the fuel mixture containing ethanol and bio-diesel as an alternative fuel has been carried out. This report deals with the exhaust emission of bio-diesel on twin cylinder diesel engine. The objectives of this report are to analyse the fuel consumption and the emission characteristic of a twin cylinder diesel engine that are using bio-diesel obtained from Jatropha plant seeds compared to usage of ordinary diesel that are available in the market. This report describes the setups and the procedures for the experiment which is to analyse the emission characteristics and fuel consumption of diesel engine due to usage of the both fuels. Detail studies about the experimental setup and components have been done before the experiment started. Data that are required for the analysis is observed from the experiments. Calculations and analysis have been done after all the required data needed for the thesis is obtained. The experiment used diesel engine with no load conditions. A four stroke Twin cylinder diesel engine was adopted to study the brake thermal efficiency, brake specific energy consumption, mechanical efficiency, brake power, volumetric efficiency, indicated thermal efficiency and emissions at full load with the fuel of fraction ethanol in bio-diesel. In this study, the diesel engine was tested using ethanol blended with bio-diesel at certain mixing ratios of (B:E)- 75:25, 70:30 ethanol to bio-diesel respectively with the addition of diesel additive available in the store for trouble free starting. Reduces knock, noise, misfiring, shock load and engine wear. It reduces knock, noise, misfiring, shock load and engine wear. By the end of the report, the successful of the project have been started which is Kirloskar engine is able to run with bio-diesel blend but the engine needs to run by using diesel fuel first, then followed by bio-diesel blend and finished with diesel fuel as the last fuel usage before the engine turned off. The performance of the engine using blended fuel compared to the performance of engine with diesel fuel. Experimental results of blended fuel and diesel fuel are also compared.